ANTARA INDUSTRI KREATIF DAN PARIWISATA HALAL DALAM PERSPEKTIF HUKUM (STUDI KASUS KOTA SEMARANG) - Andi Fariana; Krishna Ihza Mahendra (Prodi Hukum Keluarga Islam (Ahwal Asy-Syakhsiyyah) Fakultas Syariah Unisba, 2021)
The creative industry is one of the sectors that can support halal tourism, so it is difficult to separate the creative industry from tourism. The purpose of this study is to explore how laws and regulations (including regional regulations) provide support to develop the great potential that exists in the creative and tourism industries. Constitution number 10 of 2009 about Tourism, Constitution number 24 of 2019 about the Creative Economy and Constitution number 11 of 2021 about Job Creation have become the legal coverage for Regional Governments to develop tourism and creative industries in their regions. Central Java, where the city of Semarang as one of the halal tourism destinations has taken the right step by issuing Regional Regulation Number 10 of 2012 about the Master Plan for Tourism Development and Regional Regulation Number 5 of 2021 about Creative Economy Development, to support the existing Regional Regulations, various other policies that are more operational in nature so that there is an acceleration in the development of the creative industry and halal tourism and in the end can increase the economic growth of the community. Keywords: creative, industry, halal, tourism, law.